Indonesian e-Agriculture Strategic Framework: A Direction of ICT Usage as Enabler in Agriculture - Rubhasy, Albaar; Hasibuan, Zainal Arifin (Jurnal Informatika dan Komputasi STMIK Indonesia Jakarta, 2012)
As indicated in many studies, a modern agriculture posts several problems. It tends to not environmentally friendly due to chemical usage, produced more waste, and the land is forced to produced exceeding its capacity. Beside that in the modern agricultural supply chain, farmers (producers) always in a weaker position as compare to distributors (intermediaries) and costumers. Lack of access to updated information leads to a poor judgment on what to plant, when to plant, how much to plant, and where to sale. This imbalanced of agricultural supply chain reduced the farm profitability. Furthermore, it creates a structured poverty in the farming communities due to weakened processes of farming resources ability to fulfill sufficient needs. ICTs could help small and medium farmers increase their revenues (which is related to farm profitability), improve their farming practices (which is related to environmental stewardship), and making it possible for them to access information on agricultural know-how through knowledge sharing among them (which is related to prosperous farming communities), and through research center. ICT can help to increase transparency, prevent corruption, optimal price discovery, information dissemination, usability, preservation and management of documents and content. However, it requires network and information security, interoperability, standardization of business processes and for localization and internationalization of content. All these components need to be structured in such a way into an Indonesian E-Agriculture Strategic Framework (IESF). IESF aims at deploying ICTs for sustainable development in agriculture area targeting ultimate beneficiaries (i.e. farmers) by providing direct-link among farmers, merchants, consumers, local governments with global markets, research center, banks, and so forth. Keywords: agricultural supply chain; E-Agriculture